Schiff-base macrocyclic ZnII complexes based upon flexible pendant-armed extended dialdehydes. Issue 2 (22nd November 2018) - Chang, Fei-Fan; Zhang, Kun; Huang, Wei
Abstract : This Frontier article reviews Schiff-base Zn II macrocycles derived from flexible pendant-armed extended dialdehydes including structure-determining factors in template-directed syntheses, further post-modifications and applications. Abstract : This Frontier article reviews diverse structures of Schiff-base macrocyclic Zn II complexes derived from a family of flexible pendant-armed extended dialdehydes via a preorganized synthetic strategy and the corresponding structure-determining factors, including primary cationic template effects and secondary complementary template effects. In addition, further post-modification and supramolecular self-assembly of Schiff-base Zn II macrocycles and their possible applications in a variety of areas have been discussed.